UPAYA MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN BAHASA INDONESIA DENGAN MENGGUNAKAN MEDIA BIG BOOK PADA PESERTA DIDIK KELAS I SDN 24 TEMMALEBBA KOTA PALOPO - Misrawati Misrawati (IAIN Palopo, 2018)
This research aims to determine the improvement of beginning skill through big book media on the students of class I SDN 24 Temmalebba Palopo city. This research uses the qualitative and quantitative approach with Classroom Action Research (PTK) which is designed through two cycles. Research subjects, students of SDN 24 Temmalebba class I which amounted to 28 students. Data collection techniques used, namely observation, documentation, and tests. The research data obtained were analyzed by using descriptive statistic formula (percentage) to express descriptively the research result. Furthermore, to discuss and explain the results of research that is quantitative descriptive then used the technique of data reduction analysis, data presentation, and drawing a conclusion. The research results found that in precycle stage, with the average value of reading skill beginning is 51,5 with mastery learning classical 25%. After implementing the learning by applying the big book media, in the first cycle, the average score of reading skill is 66.71 students with 57.14% classical learning completeness. Furthermore, in cycle II with the average score of simple writing skill is 75.21 with 89.28% classical learning completeness. Thus, the initial reading skill in class I SDN 24 Temmalebba Palopo City by applying the big book media conducted from the first cycle to the 2 show significant results. Therefore, the big book media needs to be referenced by the teacher in the activity.